Developmental Changes in the Relationship Between Character Reading Ability and Orthographic Awareness in Chinese - Lin, Dan; Mo, Jianhong; Liu, Yingyi; Li, Hong (Frontiers in Psychology, 2019)
The present study examined developmental changes, over a six-year period, in the relationship between character reading ability and orthographic awareness in Chinese from the first year of kindergarten to the third year of primary school in two separate samples: the kindergarten sample of 96 children was assessed three times in the first, second and third years of kindergarten (K1, K2, K3) with 12-month intervals. The primary school sample of 204 children was assessed four times in the first and second semesters of grade 1 (P1-S1; P1-S2), first semester of grade 2 (P2-S1) and grade 3 (P3-S1), with the first three waves at 6-month intervals and the final wave at 12-month interval. Cross-lagged path analysis showed three developmental stages of the relationship between Chinese character reading and orthographic awareness. At stage 1, reading ability in K1 and K2 predicted subsequent orthographic awareness in K2 and K3. At stage 2, there was a bidirectional relationship between character reading and orthographic awareness from P1-S1 to P1-S2. At stage 3, orthographic awareness at P1-S2 and P2-S1 predicted subsequent character reading ability at P2-S1 and P3-S1, but the prediction from reading to orthographic awareness vanished at this stage. The results depict a full developmental picture of the changed relationship between Chinese character reading and orthographic awareness over time. Beginning readers demonstrated impressive abilities in discovering or extracting orthographic regularities with increased reading ability.